2017
DOI: 10.1097/cin.0000000000000331
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Nurses’ Strategies to Handle (Un)wanted Nurse Calls

Abstract: Nurse calls in a hospital can constitute either positive or negative (wanted or unwanted) interruptions depending on various factors. This study aims to understand nurses' strategies in facilitating the reception of wanted nurse calls and the restriction of unwanted nurse calls. Applying a resilience engineering perspective, nurses' performance variability is investigated as a basis to design appropriate computer support to enhance efficiency and patient safety. A qualitative case study was conducted for a per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Patient care system alarms, by nature, are a source of interruption for nurses [ 4 , 21 , 24 ]. These interruptions have been shown as a potential contributory factor leading to medical errors in clinical environments [ 31 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patient care system alarms, by nature, are a source of interruption for nurses [ 4 , 21 , 24 ]. These interruptions have been shown as a potential contributory factor leading to medical errors in clinical environments [ 31 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have tried to reduce medical errors by reducing the frequency of interruptions, the effect and safety of which, however, remain questionable [ 21 , 34 , 35 ]. The main reason for this may be due to the complex nature of interruptions in hospital settings, in which not all interruptions are undesirable [ 14 , 17 , 20 , 24 ]. Moreover, patients think that it is essential that their requests are taken seriously and that they can receive support whenever needed [ 2 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shiferaw (2020) exclaims Leaders of nursing teams ought to impose workflow conductive by limiting the non-urgent interruptions and guide nurses to mitigate obstructions lead to patient harm cause experience to become worse. Training will adapt strategies to avoid interruption minimize the risk of healthy injury research (Klemets & Evjemo, 2017) concluded that interruptions directly link performance variability to significantly unwanted and wanted interruptions. Health care resilience aligned by responding to non-avoidable distractions and avoiding unnecessary.…”
Section: Discussionmentioning
confidence: 99%
“…The difference between "work as imagined" and "work as done" forced nurses to be resilient and change their work as done with the new system to create the desired effect. 26 Our study has some potential weaknesses. Participants in the focus groups were not entirely randomly selected.…”
Section: Figurementioning
confidence: 91%